Moralisations of Space and the Spatiality of Morality - Alina Bezlaj (Svetovi, 2025)
Recent scholarship on morality highlights it as a communal and everyday achievement, rooted in everyday (spatial) practices and tied to places. In this article, I explore two distinct yet overlapping moral orders that shape life in Ballymun, a working-class suburb of Dublin built in the 1960s as a social housing estate and redeveloped in the early 2000s. I argue that these moral repertoires correspond to two versions of Ballymun: the pre-regeneration “Old Ballymun” and the post-regeneration “New Ballymun”. Both places are morally charged and thus often generate conflicting understandings of the neighbourhood and its challenges. While regeneration, driven by the neoliberal politics of the Third Way, sought to materially and socially transform the area through new moral visions, these were not uniformly adopted by residents. Some embraced them; others resisted, drawing instead on affective and memorial ties to Old Ballymun and leaning on the moral repertoires tied to the past place. Although the moral logics of old and new often align, they also produce tensions – particularly around notions of individual responsibility, care, and the causes of local problems. I show in this article how moral values are embedded in everyday practices that shape the neighbourhood, and how different conceptions of place inform residents’ moral interpretations of its transformation and ongoing struggles.